Repeated measures of body mass index and C-reactive protein in relation to all-cause mortality and cardiovascular disease: results from the consortium on health and ageing network of cohorts in Europe and the United States (CHANCES) - O'Doherty, Mark; Brenner, Hermann; Schöttker, Ben (European journal of epidemiology, 2014)
Obesity has been linked with elevated levels of C-reactive protein (CRP), and both have been associated with increased risk of mortality and cardiovascular disease (CVD). Previous studies have used a single ‘baseline’ measurement and such analyses cannot account for possible changes in these which may lead to a biased estimation of risk. Using four cohorts from CHANCES which had repeated measures in participants 50 years and older, multivariate time-dependent Cox proportional hazards was used to estimate hazard ratios (HR) and 95 % confidence intervals (CI) to examine the relationship between body mass index (BMI) and CRP with all-cause mortality and CVD. Being overweight (≥25-<30 kg/m2) or moderately obese (≥30-<35) tended to be associated with a lower risk of mortality compared to normal (≥18.5-<25): ESTHER, HR (95 % CI) 0.69 (0.58-0.82) and 0.78 (0.63-0.97); Rotterdam, 0.86 (0.79-0.94) and 0.80 (0.72-0.89). A similar relationship was found, but only for overweight in Glostrup, HR (95 % CI) 0.88 (0.76-1.02); and moderately obese in Tromsø, HR (95 % CI) 0.79 (0.62-1.01). Associations were not evident between repeated measures of BMI and CVD. Conversely, increasing CRP concentrations, measured on more than one occasion, were associated with an increasing risk of mortality and CVD. Being overweight or moderately obese is associated with a lower risk of mortality, while CRP, independent of BMI, is positively associated with mortality and CVD risk. If inflammation links CRP and BMI, they may participate in distinct/independent pathways. Accounting for independent changes in risk factors over time may be crucial for unveiling their effects on mortality and disease morbidity.
Gesehen am 29.10.2020